KOMPOTENSI TEKNIS PETANI DALAM BUDIDAYA PADI SAWAH DI KELURAHAN BARUGA KECAMATAN BARUGA KOTA KENDARI - Wahab, Rifli; Abdullah, Sukmawati; Arif, La Ode Kasno (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2025)
Competence is defined as the skills and knowledge from the social environment that are mastered and used by performing work as well as possible. The objective of this study is to assess the technical proficiency of farmers in rice cultivation in Baruga Village, Baruga District, Kendari City. The population of this study comprised rice farmers residing in Baruga Village, constituting a total population of 278 individuals. The sample size was determined by allocating 10% of the total population, yielding a sample of 27 individuals. The sample was obtained through the implementation of simple random sampling. The research variable was the technical competence of farmers in rice cultivation. The data were analyzed using quantitative descriptive analysis. The findings indicated that the technical proficiency of rice farmers in Baruga Village was, on the whole, satisfactory. The farmers demonstrated particular expertise in seed selection, sowing, maintenance, and harvesting. However, variations in land preparation, planting, and fertilization were observed, with these practices proving adequate for only a subset of farmers. It is imperative to enhance the competencies of farmers, particularly during the nascent stages of cultivation, to ensure productivity.